Estudio de la participación de la mitocondria y de la proteína P53 en la muerte de las células de insulinoma inducida por concentraciones elevadas de glucosa - Ortega Camarillo, Clara (Universidad Autónoma Metropolitana, 2006)
The mechanism by which hyperglycemia induces pancreatic β cell apoptosis is not completely understood. However, it is known that chronic states of hyperglycemia promote a state of oxidative stress that activates the p53 protein which participates in cell survival. The aim of this study was to find whether oxidative stress generated by hyperglycemia was the cause of RINm5F cell apoptosis via the translocation of p53 to the mitochondria. In order to carry this out, insulin producing cells (RINm5F) were cultured in RPMI 1640-SFB 10% medium in the presence of 11 or 30 mM glucose for 30 minutes, 2, 4, 24 or 48 hours. Apoptosis was assessed using flow cytometry through the staining of cells with annexin-V-FITC and propidium iodide (PI). Additionally, DNA integrity was analyzed using electrophoresis in agarose gel. The reactive oxygen species (ROS), as well as their origin, were detected using dichlorodihydrofluorescein diacetate (DCDHF-DA) in the presence of rotenone 5 μM (mitochondrial complex I inhibitor), cccp 0.1 μM (de-coupler of oxidative phosphorylation) and apocinine 10 μM (NADPH oxidase inhibitor). For the purpose of assessing intracellular p53 distribution and the release of cytochrome c, a Western Blot test and confocal microscopy was done for which the mitochondria were stained with MitoFluor 589 and p53 with a specific antibody. The changes in mitochondrial membrane potential were estimated through the fluorescent changes of the JC-1 stain (R&D Systems Kit). The results demonstrated that short term high glucose concentrations (30 minutes, 2, 4 and 24 hours) is not a strong stimulus for inducing apoptosis in RINm5F cells, since no changes were detected in the percentage of cells positive to annexin V-FITC/negative to PI (7.52 ± 0.89 and 9.53 ± 1.03, control and at 24 hours, respectively). A significant increase in this cell population (36 ± 11.3%) was seen only at 48 hours of incubating with glucose 30 mM. These events correlate with the DNA oligonucleosomal fragmentation from these same cells. In addition, a 2.5 fold increase was seen with respect to the control (67.32 ± 7.54 and 175.6 ± 18.3, respectively) in the production of mitochondrial ROS under hyperglycemic conditions with an important contribution of NADPH oxidase system. The Western blot analysis showed the presence of p53 in mitochondria, and by confocal microscopy, it was determined that this protein is located in mitochondria within the first 24 hours of incubating with 30 mM of glucose, with further increase at 48 hours. Modifications on mitochondrial permeability are confirmed by changes in JC-1 fluorescence using confocal microscopy and the cytosolic release of cytochrome c. Based on these results, we can conclude that under oxidative stress conditions due to hyperglycemia, protein p53 moves towards the mitochondria and induces changes in the membrane potential and the release of cytochrome c, finally leading to the apoptosis of RINm5F cells.; El mecanismo mediante el cual la hiperglucemia induce la apoptosis de las células β pancreáticas no está completamente entendido. Sin embargo, se sabe que la hiperglucemia crónica promueven un estado de estrés oxidativo que activa a la proteína p53, la cual participa en la regulación de la supervivencia celular. El presente trabajo pretende conocer si el estrés oxidativo generado por hiperglucemia esta relacionado con la apoptosis de las células RINm5F vía translocación de p53 hasta la mitocondria. Con este propósito se cultivaron células productoras de insulina (RINm5F) en medio RPMI 1640-SFB 10%, en presencia de 11 ó 30 mM de glucosa durante 30 minutos, 2, 4, 24 y 48 h. La apoptosis se evaluó mediante citometría de flujo por tinción de las células con anexina-V-FITC e ioduro de propidio (IP); de forma adicional se analizó la integridad del DNA por electroforesis en gel de agarosa. Las especies reactivas de oxígeno (ERO), así como su origen se detectaron con la sonda 2’,7’– diacetato de diclorodihidrofluoresceína (DCDHF-DA) en presencia de: rotenona 5μM (inhibidor del complejo I mitocondrial), cccp 0.1μM (desacoplador de la fosforilación oxidativa) y apocinina 10μM (inhibidor de la NADPH oxidasa). Con el propósito de conocer la distribución intracelular de p53 y la liberación de citocromo c se realizó un estudio por “Western blot” y por microscopia confocal para lo cual se tiñeron las mitocondrias con MitoFluor 589 y p53 con un anticuerpo específico. Los cambios en el potencial de membrana mitocondrial se estimaron mediante los cambios en la fluorescencia del colorante JC-1 (Estuche de R&D Systems). Los resultados demostraron que la concentración alta de glucosa a tiempos cortos (30 minutos, 2, 4 y 24 h), no es un estimulo suficiente para inducir apoptosis en las células RINm5F; ya que no se observaron cambios en el porcentaje de células positivas a anexina V-FITC/negativas a IP (7.52± 0.89 y 9.53±1.03, control y a las 24 h, respectivamente) Un aumento significativo en esta población celular (36±11.3%) se observó únicamente a las 48 h de cultivo con 30 mM de glucosa, estos eventos correlacionaron con la fragmentación oligonucleosomal del DNA proveniente de estas mismas células. Además se observó un aumento de 2.5 veces con respecto al control (67.32±7.54 y 175.6±18.3 respectivamente) en la producción de ERO de origen mitocondrial, con una importante contribución por parte de la NADPH oxidasa en condiciones de alta glucosa. El análisis por “Western blot” reveló la presencia de p53 en las mitocondrias y por microscopía confocal se dterminó que esta proteína puede localizarse en las mitocondrias a partir de las 24 h de cultivo con 30 mM de glucosa, con un incremento a las 48 h. Las modificaciones en la permeabilidad mitocondrial se confirmaron por los cambios en la fluorescencia de JC-1 mediante microscopía confocal y por la liberación citosólica de citocromo c. Con base en estos resultados podemos concluir que en condiciones de estrés ox.idativo por alta glucosa, la proteína p53 se moviliza hacia la mitocondria e induce cambios en el potencial de membrana y la liberación de citocromo c, llevando finalmente a la apoptosis de las células RINm5F.